2018
DOI: 10.5001/omj.2018.36
|View full text |Cite
|
Sign up to set email alerts
|

Screening Questionnaires for Obstructive Sleep Apnea: An Updated Systematic Review

Abstract: Obstructive sleep apnea (OSA) is the most common sleep-related breathing disorder and is associated with significant morbidity. We sought to present an updated systematic review of the literature on the accuracy of screening questionnaires for OSA against polysomnography (PSG) as the reference test. Using the main databases (including Medline, Cochrane Database of Systematic Reviews and Scopus) we used a combination of relevant keywords to filter studies published between January 2010 and April 2017. Populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
103
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 53 publications
0
103
1
4
Order By: Relevance
“…Indeed, PSG/PG is an expensive and time-consuming procedure and it was shown that the STOP questionnaire reliably and accurately identifies subjects in the general population with increased risk of OSA. 33,50 Considering the high sensitivity of the STOP questionnaire, 51,52 which was also established in our previous study, 27 we decided not to perform an expensive and time-consuming procedure such as PSG/PG in all control group respondents, in order to minimize medical costs and unnecessary medical procedures in patients not at risk. Accordingly, if the assessment with the use of STOP questionnaire resulted in asymptomatic undiagnosed OSA patients included in the control group, the difference between controls and cases would be even more diminished and more difficult to find.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PSG/PG is an expensive and time-consuming procedure and it was shown that the STOP questionnaire reliably and accurately identifies subjects in the general population with increased risk of OSA. 33,50 Considering the high sensitivity of the STOP questionnaire, 51,52 which was also established in our previous study, 27 we decided not to perform an expensive and time-consuming procedure such as PSG/PG in all control group respondents, in order to minimize medical costs and unnecessary medical procedures in patients not at risk. Accordingly, if the assessment with the use of STOP questionnaire resulted in asymptomatic undiagnosed OSA patients included in the control group, the difference between controls and cases would be even more diminished and more difficult to find.…”
Section: Discussionmentioning
confidence: 99%
“…STOP-BANG questionnaire was used to screen most of our subjects who presented for preoperative evaluation prior to having PSG done in those who had elevated scores, but we did not compare the association of OSA with STOP-BANG in our analysis. The STOP-BANG has been shown in multiple studies to show a high level of sensitivity for predicting moderate and severe OSA however the Positive predictive value is not very good because of its low specificity [28][29][30]. Berlin questionnaire is another proposed screening tool for OSA but its performance for detecting sleep apnea in the middleaged general population has been questioned [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…46 Many sleep assessment tools are weighted heavily in favor of the male gender in regards to being at risk for OSA. 45,47 Researchers now know that women and children are also at risk for poor sleep quality for environmental and systemic health reasons. 6,16,9,26,29 Also, a patient's lifestyle, health history, and oral assessments might indicate a poor sleep condition that is not related to an obstructed airway.…”
Section: Screening Tools For Sleep Disruptorsmentioning
confidence: 99%